A Brief analysis of emergy for rubber plantation ecosystem of Hainan state farms - Zhongliang Tao; Jusheng Jiang; Ruibo Li (Proceedings of IRRDB Conference: NR Industry: Responding to Globalization, 7-8 September 2004, Kunming International Convention & Exhibition Center, China. pp.188-192.)
Applying emergy analysis theory and method, the emergy in the ecosystem of rubber plantation of HSFB in 2002 is analysed and evaluated briefly. The results show that the ecosystems emergy yield ratio is 4.42, the emergy investment ratio is 2.37 and the environmental loading ratio is 2.40. These data indicate that the environmental resource utilization ratio of the rubber plantation of HSFB is high, the investment price is low and the pressure to environmental resources is slight. In the ecosystems emergy investment, chemical fertilizer accounts for 62.07;of the total investment and it indicates that the ecosystems productivity doesnt have too much dependence on the natural soil fertility, so there is great space for improving productivity by increasing organic emergy input. In the ecosystems emergy output, living rubber wood accounts for 82.0;in the total investment, so rubber tree processing and utilization has great potential and should pay much more attention to it.
Keywords: Emergy analysis; Emergy evaluation; Hainan; Rubber plantation